Changes in the disposition of oxcarbazepine and its metabolites during pregnancy and the puerperium - ONAT, FİLİZ (WILEY, 2006)
Purpose: To determine potential changes in the plasma concentrations of oxcarbazepine (OXC) and its metabolites during pregnancy and puerperium. Methods: Five women receiving OXC monotherapy were followed prospectively during pregnancy and the puerperium. Four women were enrolled in the first trimester, and one woman, 2 weeks before delivery. Steady-state concentrations of OXC, its active R-(-)- and S-(+)-monohydroxy derivatives (MHD), and the additional metabolite carbamazepine-10,11-trans-dihydrodiol (DHD) were measured at regular intervals by an enantioselective HPLC assay. Results. In all samples, S-(+)-MHD was the most abundant compound in plasma and accounted almost entirely for the amount of active moiety (defined as the molar sum of OXC, R-(-)-MHD, and S-(+)-MHD) found in the circulation. The dose-normalized concentrations of active moiety decreased markedly during gestation and, in four of the five patients, increased strikingly after delivery. Plasma concentrations of S-(+)-MHD mirrored closely the levels of the active moiety. Plasma concentrations of the parent drug and other metabolites also tended to decrease during pregnancy and to increase after delivery. Conclusions: During treatment with OXC, S-(+)-MHD is by far the most abundant active compound in plasma. The concentration of this metabolite as well as the active moiety may decrease markedly during pregnancy and may increase severalfold after delivery. Because of these striking pharmacokinetic changes, the clinical response should be monitored closely in OXC-treated women throughout pregnancy and the puerperium.
Keywords: oxcarbazepine; monohydroxycarbazepine; pregnancy; puerperium; pharmacokinetics; enantiomers; therapeutic drug monitoring; LAMOTRIGINE PLASMA-LEVELS; PHARMACOKINETICS; 10-HYDROXYCARBAZEPINE; LACTATION